The Pelagic Bacterium Paraphotobacterium marinum Has the Smallest Complete Genome Within the Family Vibrionaceae - Huang, Zhaobin; Liu, Zhen; Shao, Zongze (Frontiers in Microbiology, 2017)
Members of the family Vibrionaceae are metabolically versatile and ubiquitous in natural environments, with extraordinary genome feature of two chromosomes. Here we reported the complete genome of Paraphotobacterium marinum NSCS20N07DT, a recently described novel genus-level species in the family Vibrionaceae. It contained two circular chromosomes with a size of 2,593,992 bp with G+C content of 31.2 mol%, and a plasmid with a size of 5,539 bp. The larger chromosome (Chr. I) had a genome size of 1,426,504 bp with G+C content of 31.6 mol%, and the smaller one (Chr. II) had a genome size of 1,161,949 bp with G+C content of 30.8 mol%. The two chromosomes have strikingly similar G+C contents with difference of <1% and similar percentages of coding regions. Interestingly, by comparison to 134 species affiliated with 7 genera within the family Vibrionaceae, P. marinum NSCS20N07DT possessed the smallest genome size and lowest G+C content. COG functional categories revealed that the two chromosomes had different distributions of functional classes, indicating they take different cellular functions. Surprisingly, Chr. II had a large proportion of unknown genes than Chr. I. Metabolic characteristics predicted that Chr. I performed the essential metabolism, which can be complemented by the Chr. II, such as amino acids biosynthesis. Microbial community analysis of in situ surface seawater revealed that P. marinum accounted for 1 to 4 sequences among more than twenty thousands of 16S rRNA gene V4 contigs, representing it apparently appeared as a rare species. What’s more, P. marinum was anticipated to be specific to the pelagic ocean. This study will provide new insight into more understanding the genomic and metabolic features of multiple chromosomes in prokaryote and emphasize the ecological distribution of the members in the family Vibrionaceae as a rare species.